Management Evaluate and Review Solutions to Reduce Soil Pollution - Mohammad Beykzade; Sepide Beykzade (LPPM ITK, 2020)
Crude oil is a complex natural mixture that is one of the main sources of energy for life. Oil pollution has unpleasant effects on the environment that can cause many problems for human beings, since the toxicity and carcinogenesis of oil compounds for living creatures and humans are obvious and proven. The oil-contaminated soils and waters are one of the most important environmental issues. Scientists have proved different ways to clean up oil pollution throughout history. In this research, ways to reduce and eliminate pollution of crude oil in the soil are going to be studied. The following methods are suggested : The use of electrochemical methods for reducing the aromatic contamination of crude oil, The use of biodegradable and synthetic detergents for the removal of oil hydrocarbons, bioremediation of soil contaminated with plants. Finally, by reviewing the results obtained, solutions can be found to clean up the pollution of crude oil from the soil, Because cleaning up crude from soil reduces environmental degradation.